PALEOVOLCANIC KARING RECONSTRUCTION IN THE MERANGIN JAMBI UNESCO GLOBAL GEOPARK TERRITORY BASED ON PETROLOGICAL AND GEOCHEMICAL APPROACH - utama, hari wiki; Sutarto, Sutarto; Widagdo, Asmoro; Wahyudi, Eko (JOURNAL ONLINE OF PHYSICS, 2023)
The presence of lava and pyroclastic sequences in the Karing River on the Merangin Jambi UNESCO Global Geopark territory provides information about the existence of ancient volcanoes. The absence of confirmed rock formations from the distribution of volcanic rock products that have been mapped nationally and also the shape of this ancient volcanic body, is an important reason for this research to be carried out using a petrological approach using petrography and XRF gochemical methods. Petrographic analysis is an appropriate method to determine the mineralogy consist, textures and particular textures, rock structures that are confirmed from field data. Meanwhile, a geochemical approach is used to determine rock oxide compounds. This method aims to reconstruct the shape and type of volcanoes. Research data shows that there are four lava sequences, with Sequence 1 having an entablature structure, Sequence 2 and Sequence 3 having a flow structure, and Sequence 4 having a vesicular-flow structure. The petrography results show that Sequence 1 and Sequence 2 are composed of phenocrysts and microliths of plagioclase, olivine, clinopyroxene, orthopyroxene. Meanwhile, in Sequence 3, hornblende is present, and in Sequence 4, the mineral olivine is absent. The results of geochemical analysis from the four lava sequences are in basalt rocks with 40%-50% Silica content, Calk-alkali basalt magma series, petrogenesis interpreted from the convergence of oceanic subduction beneath continent. The pyroclastic rocks found at the bottom of the lava sequence are evidence of the stratigraphic structure that makes up a volcano originating from the Karing Paleovolcanic, while the pyroclastic rocks found at the top of the lava sequence are believed to originate from other ancient volcanic eruptions. With the stratigraphy composed of lava and pyroclastic sequences, it can be concluded that this ancient volcano is a strato volcano type which is relatively sloping and almost resembles a shield volcano.